Muscimol-induced inactivation of the anterior cingulate cortex does not impair trace fear conditioning in the rat - Pezze, Marie A (J Psychopharmacol, 2020)
Previous studies suggest that trace conditioning depends on the anterior cingulate cortex (ACC). To examine the role of ACC in trace fear conditioning further, 48 rats were surgically prepared for infusion with saline or 62.5 or 125 µg/side muscimol to inactivate ACC reversibly prior to conditioning. A noise stimulus was followed by a 1 mA footshock, with or without a 10-second trace interval between these events in a conditioned suppression procedure. The trace-conditioned groups (10 seconds) showed less test suppression than the control-conditioned groups (0 seconds). Counter to prediction, there was no effect of muscimol infusion on suppression to the noise stimulus in the 10-second trace groups.